The Phenoxyphenol Compound diTFPP Mediates Exogenous C2-Ceramide Metabolism, Inducing Cell Apoptosis Accompanied by ROS Formation and Autophagy in Hepatocellular Carcinoma Cells - Wen-Tsan Chang; Yung-Ding Bow; Yen-Chun Chen; Chia-Yang Li; Jeff Yi-Fu Chen; Yi-Ching Chu; Yen-Ni Teng; Ruei-Nian Li; Chien-Chih Chiu (MDPI AG, 2021)
Hepatocellular carcinoma (HCC) is a severe disease that accounts for 80% of liver cancers. Chemotherapy is the primary therapeutic strategy for patients who cannot be treated with surgery or who have late-stage HCC. C2-ceramide is an effective reagent that has been found to inhibit the growth of many cancer types. The metabolism of C2-ceramide plays a vital role in the regulation of cell death/cell survival. The phenoxyphenol compound 4-{2,3,5,6-tetrafluoro-4-[2,3,5,6-tetrafluoro-4-(4-hydroxyphenoxy)phenyl]phenoxy}phenol (diTFPP) was found to have a synergistic effect with C2-ceramide, resulting in considerable cell death in the HA22T HCC cell line. diTFPP/C2-ceramide cotreatment induced a two- to threefold increase in cell death compared to that with C2-ceramide alone and induced pyknosis. Annexin V/7-aminoactinomycin D (7AAD) double staining and Western blotting indicated that apoptosis was involved in diTFPP/C2-ceramide cotreatment-mediated cell death. We next analyzed transcriptome alterations in diTFPP/C2-ceramide-cotreated HA22T cells with next-generation sequencing (NGS). The data indicated that diTFPP treatment disrupted sphingolipid metabolism, inhibited cell cycle-associated gene expression, and induced autophagy and reactive oxygen species (ROS)-responsive changes in gene expression. Additionally, we assessed the activation of autophagy with acridine orange (AO) staining and observed alterations in the expression of the autophagic proteins LC3B-II and Beclin-1, which indicated autophagy activation after diTFPP/C2-ceramide cotreatment. Elevated levels of ROS were also reported in diTFPP/C2-ceramide-treated cells, and the expression of the ROS-associated proteins SOD1, SOD2, and catalase was upregulated after diTFPP/C2-ceramide treatment. This study revealed the potential regulatory mechanism of the novel compound diTFPP in sphingolipid metabolism by showing that it disrupts ceramide metabolism and apoptotic sphingolipid accumulation.